Current Approach to Menopause - Sena Sayan; Recep Yildizhan (Van Tıp Dergisi, 2017)
With the increase in the life span, the period of physiological menopause also extends. Many health problems, especially vasomotor symptoms, will develop in the period of menopause. Therefore, the medical and paramedical methods developed are frequently updated. While not being prescribed as often as in previous years, hormone replacement therapy is still the most important method for relieving these symptoms.